2002
DOI: 10.1093/geronb/57.6.p501
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to Aging Losses: Do Resources Facilitate Strategies of Selection, Compensation, and Optimization in Everyday Functioning?

Abstract: Previous cross-sectional research has shown that older people who are rich in sensorimotor-cognitive and social-personality resources are better functioning in everyday life and exhibit fewer negative age differences than resource-poor adults. Longitudinal data from the Berlin Aging Study was used to examine these findings across a 4-year time interval and to compare cross-sectional indicators of adaptive everyday functioning among survivors and nonsurvivors. Apart from their higher survival rate, resource-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
136
2
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(156 citation statements)
references
References 9 publications
12
136
2
6
Order By: Relevance
“…For example, the present analyses did not include personality and social resource variables that may also affect everyday competence [1][2]4]. These factors should be addressed in future research on this topic.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, the present analyses did not include personality and social resource variables that may also affect everyday competence [1][2]4]. These factors should be addressed in future research on this topic.…”
Section: Discussionmentioning
confidence: 95%
“…Such competence and the ability to continuously adapt to changing circumstances depend on assets in a variety of domains, including sensory, sensorimotor, cognitive, personality, and social resources [1][2]4]. Sensory resources refer to pure sensory processes, such as vision and hearing, while sensorimotor resources refer to functions that closely integrate sensory input and motor skills (e.g., balance, gait).…”
Section: Introductionmentioning
confidence: 99%
“…Without an understanding of clients' perspectives on how depression affects their daily life activities, practitioners lack the contextual perspective necessary to assess clients with depression and determine interventions that will be most effective for supporting everyday activities and functioning (Lang, Rieckmann, & Baltes, 2002). To provide insight into the dynamics of activity engagement, this descriptive study examined daily life activities of older adults during a depressive episode using an interactive qualitative assessment method (Sandelowski, 2000).…”
mentioning
confidence: 99%
“…The so far most frequently used instrument is a selfreport questionnaire (SOC questionnaire, Freund & Baltes, 2002b). Other indicators have been derived, for example, from minuteto-minute reconstructions of the sequence, duration, geographical, and social context of everyday activities (Baltes & Lang, 1997;Lang, Rieckmann, & Baltes, 2002), from content analyses of strategies employed to cope with disability (Bouchard Ryan et al, 2003;Gignac, Cott, & Badley, 2000, or from patterns of self-reported resource investment in various domains of life (e.g., Staudinger & Freund, 1998;Staudinger et al, 1999;Wiese, 2000;Wiese & Freund, 2000).…”
Section: The Meta-model Of Selection Optimization and Compensationmentioning
confidence: 99%
“…In support of the assumption that engagement in SOC strategies is resource intensive, studies have shown that resource-rich individuals tend to exhibit higher levels of engagement in SOC strategies than resource-poor individuals (Baltes & Lang, 1997;Jopp, 2002;Lang et al, 2002). Furthermore, there is accumulating evidence that engagement in SOC-related life management strategies is particularly effective when resources are limited (Abraham & Hansson, 1995;Chou & Chi, 2002;Jopp, 2002;Staudinger & Freund, 1998;Staudinger et al, 1999).…”
Section: The Meta-model Of Selection Optimization and Compensationmentioning
confidence: 99%